Pengaruh Variabel Makroekonomi terhadap Jakarta Islamic Index (JII) periode Januari 2004 Hingga Desember 2017 - Rubina Dwi Ghassani; Raditya Sukmana (Universitas Airlangga, 2019)
This study aims to determine the effect of Macroeconomic Variables against the sharia stock index, Jakarta Islamic Index. The approach used is quantitative by using the Vector Error Correction Model (VECM) analysis technique with the STATA program. While the Exchange Rates, Industrial Production Index and Money Supply as dependent variables and Jakarta Islamic Index (JII) as the independent variable. Secondary data are used in this research from the official website of Bank Indonesia, Badan Pusat Statistik and Bursa Efek Indonesia. The results of the research shows that the Exchange Rates, Industrial Production Index and Money Supply partially has positive and significant influent against sharia stock index in Jakarta Islamic Index (JII) di Jakarta Islamic Index on the research period is from 2004 to 2017.Keywords: Exchange Rates, Industrial Production Index, Money Supply and Jakarta Islamic Index (JII)REFERENCESAl-Bukhāri, Muhammad bin Isma’il Abu ‘Abdillah. 1422H. Shahīh al-Bukhāri juz 8 hal. 104. Beirut: Dārut Ṭūqi an-NajahAntonio, Syafii, Hafidhoh dan Himan. 2013. The Islamic Capital Market Volatility: A Comparative Between in Indonesia and Malaysia. Bulletin of Monetary, Economics and BankingAnshori, Muslich dan Sri Iswati. 2009. Metodologi Penelitian Kuantitatif. Surabaya: Airlangga University Press (AUP)an-Naisaburi, Muslim bin al-Hajjaj al-Qusyairi.Tanpa tahun.Ṣaḥīḥ Muslim juz 4 hal. 1996. Beirut: Dāru Ihyā’it’turoṡArifin, Zainal. 2003. Dasar - Dasar Manajemen Bank Syariah. Jakarta: Alphabet Aziz, Abdul. 2008. Ekonomi Islam :Analisis Mikro & Makro. Yogyakarta : Graha IlmuBadan Pusat Statistik. Indeks Produksi Bulanan Industri Besar dan Sedang. Diakses melalui www.bps.go.id/statictable/2009/08/12/1061/indeks-produksi-bulanan-industri-besar-dan-sedang.html tanggal 15 Oktober 2018Bank Indonesia. Informasi Kurs Transaksi. Diakses melalui www.bi.go.id/id/moneter/informasi-kurs/transaksi-bi/ tanggal 10 Oktober 2018———- . Uang Beredar dan Faktor-Faktor yang Mempengaruhinya. Diakses melalui www.bi.go.id/id/statistik/seki/terkini/moneter/ tanggal 10 Oktober 2018Basuki, Agus Tri dan Nano Prawoto. 2016. Analisis Regresi dalam Penelitian Ekonomi dan Bisnis : Dilengkapi Aplikasi SPSS & Eviews. Depok: PT. Rajagrafindo PersadaBeik, I. S,.& Fatmawati. 2014. Pengaruh Indeks Harga Saham Syariah Internasional dan Variabel Makro Ekonomi Terhadap Jakarta Islamic Index. Al-Iqtishad: Journal of Islamic Economics, 6(2), 155-178Bursa Efek Indonesia. Laporan Tahunan IDX Statistics. Diakses melalui www.idx.co.id tanggal 16 November 2018 Dewan Syariah Nasional (DSN) Majelis Ulama Indonesia (MUI). 2001. Fatwa Pedoman Pelaksanaan Investasi Untuk Reksa Dana SyariahDepartemen Agama Republik Indonesia. 2008. Al-Qur’an dan Terjemahan. Semarang CV. Toha PutraDunia Investasi. Indeks saham Syariah JII. Diakses melalui www.duniainvestasi.com tanggal 20 November 2018El-Nader, Hassan M, dan Ahmad Diab. 2012. The Impact of Macroeconomic Factors on Amman Stock Market Returns. International Journal of Economics and Finance, 4(12), 202.Fatwa Dewan Syariah Nasional NO.20/DSN-MUI/VI/2001 Tentang Pedoman Pelaksanaan Investasi Untuk Reksa Dana Syariah.Fatwa Dewan Syariah Nasional NO:80/DSN-MUI/III/2011 Tentang Penerapan Prinsip Syariah dalam Mekanisme Perdagangan Efek Bersifat Ekuitas Di Pasar Reguler Bursa Efek. Gujarati, Damodar. 2003. Ekonometri Dasar. Terjemahan: Sumarno Zain. Jakarta: Erlangga.Harris, R. 1995. Cointegration Analysis in Econometric Modelling. New York: Prentice Hall.Huda, Nurul. 2007. Investasi Pada Pasar Modal Syariah. Jakarta: Kencana———-. 2015. Lembaga Keuangan Islam: Tinjauan Teoritis dan Praktis. Jakarta: KencanaS. Salim. H, dan Budi Sutisno. 2008. Hukum Investasi di Indonesia. Jakarta: Rajawali Pers. L, Ahmet Tiryaki. 2017. The Causal Relationship Between Selected Macroeconomic Variables and Stock Returns in Turkey. Anandolu International Conference in Economics.Kumar, Kiran, dan Bhawna Sahu. 2017. Dynamic Linkages Between Macroeconomic factors and Islamic. The Journal of Developing AreasVol.51(1), pp 193-205.Kuncoro, M. 2001. Manajemen Keuangan Internasional. Edisi Kedua. Cetakan Pertama. Yogyakarta: BPFE. Krugman, Paul R. Maurice Obstffeld. 1999. Ekonomi Internasional Edisi ke Dua (terjemah). Jakarta, ErlanggaManan, Abdul. 2016. Hukum Ekonomi Syariah: Dalam Perspektif Peradilan Agama. Jakarta: KencanaMannan, M. A. 1993. Understanding Islamic Finance: A Study of the Securities Market in an Islamic Framework. Islamic Research and Training Institute: Saudi ArabiaMetwally, M. 1995. Teori dan Model Ekonomi Islam. Jakarta: PT. Bangkit Daya InsanaMishkin, Frederic S. 2008. The Economic Of Money, Banking and Financial Markets: Banking and Financial Markets. Jakarta: Salemba Empat.Nasional, D. P. 2002. Kamus Besar Bahasa Indonesia. Jakarta: Balai Pustaka.Otoritas Jasa Keuangan. Pasar Modal Syariah. Diakses melalui www.ojk.co.id pada 23 Septermber 2018Rosidi, Ali. 2000. Industrial Production Index, Wholesale/Producer Index, Consumer Price Index of Indonesia. Country Paper fot the Joint OECD/ESCAP Workshop on Key Economic Indicators Bangkok, 22-25 May 2000.Sakti, M. R.P dan Yousuf Harun. 2013. Relationship Between Islamic Stock Prices and Macroeconomic Variables: Evidence from Jakarta Stock Exchange Islamic Index. Global Review of Islamic Economics and Business Vol 1(1).Shihab, Q.M. 2002. Tafsir Al-Mishbah. Jakarta: Lentera HatiSugiyono. 2012. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta.Sugianto, Dergibson, dan Sugiarto. 2000. Metode Statistika; Untuk Bisnis dan Ekonomi. Jakarta: Gramedia Pustaka Utama.Sukirno, Sadono. 2013. Makroekonomi : Teori Pengantar.Jakarta : PT. Raja Grafindo PersadaSunariyah. 2010. Pengantar Pengetahuan Pasar Modal, Edisi Ke Enam. Yogyakarta: UPP AMP YKPSutedi, Adrian. 2014. Pasar Modal Syariah Sarana Investasi Keuangan Berdasarkan Prinsip Syariah. Jakarta: Sinar GrafikaSoemitra, Andri. 2014. Masa Depan Pasar Modal Syariah di Indonesia. Jakarta: KencanaThobarry, A. 2009. Analisis Pengaruh Nilai Tukar, Suku Bunga, Laju Inflasi, dan Pertumbuhan GDP terhadap Indeks Harga Saham Properti (Kajian Empiris Pada BEI Periode Pengamatan 2000-2008). Jurnal Manajemen. Universitas Diponegoro. Wahyudi, Imam dan Gandhi. 2014. Interdependence between Islamic Capital Market and Money Market: Evidence from Indonesia. Borsa Istanbul Review.Widarjono, Agus. 2007. Ekonometrika Teori dan Aplikasi. Yogyakarta: Ekonisia FE UII.